The Effect of Financial Ratio Analysis, Transfer Pricing And Corporate Social Responsibility on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2015-2019: Pengarus Analisis Rasio Keuangan, Transfer Pricing dan Corporate Social Responsibility Terhadap Penghindaran Pajak - Kristina Lelang Aya; Widi Hariyanti; Sugiarti (Profesional Muda Cendekia Publishing, 2022)
This study aims to determine the effect of financial ratios, transfer pricing, and corporate social responsibility (CSR) on tax avoidance. The design of this research is causality research which is used to prove the causal relationship of several variables. This research is a quantitative research. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The sampling method used is purposive sampling method with a sample of 27 companies during the observation period of 5 consecutive years so that the number of samples is 135. The analysis method of this study uses multiple linear regression. The results of this study indicate that profitability, level of productivity, level of sales, have no effect on tax avoidance. Meanwhile, liquidity and transfer pricing have a significant effect on tax avoidance.